First Molecular Identification of Canine Parvovirus Type 2 (CPV2) in Chile Reveals High Occurrence of CPV2c Antigenic Variant - Castillo, Cristobal; Neira, Victor; Aniñir, Pamela; Grecco, Sofia; Pérez, Ruben; Panzera, Yanina; Zegpi, Nhur-Aischa; Sandoval, Alberto; Sandoval, Daniel; Cofre, Sergio; Ortega, Rene (Frontiers in Veterinary Science, 2020)
Canine parvovirus type 2 (CPV2) is one of the most important intestinal pathogens in dogs and puppies. CPV2 has been evolved into three genetic and antigenic variants (2a, 2b, and 2c), which are distributed worldwide. We reported the first study of genetic diversity of CPV2 in Chile. Sixty-five samples were collected from puppies presenting with severe gastroenteritis and different vaccination statuses. PCR, restriction fragment length polymorphism (RFLP), and partial sequencing of the coding region of the structural viral protein VP2 was performed. Thirty of a total of 65 samples tested positive by PCR out of which 19 were further classified as CPV2c and one as CPV2a using RFLP and Sanger sequencing. The phylogeny was in concordance with the RFLP analysis. This is the first report of the genetic characterization of CPV2 in Chile and reveals a high occurrence of CPV2c.